PELAKSANAAN PENGEMBANGAN DIRI DI SMP NEGERI 23 PADANG (SEKOLAH PENYELENGGARA PENDIDIKAN INKLUSIF) - Nur Halimah (Universitas Negeri Padang, 2014)
Abstract : This research is motivated by the implementation of Extracurricular Activities or self development in SMP 23 Negeri Padang as a the inklusif school. The study aimed to determine the types of self development Activities, how to program, implementation, and evaluation at the school. This research method qualitative shape description, Data was collected by interview, observation, and documentation. Data analysis was performed during the study.